Prosaptia Contigua C. Presl (Grammitidaceae), a New Record for Vietnam - Nguyen, Cong Toan (H. : ĐHQGHN, 2019)
The specimens of genus Prosaptia C. Presl (family Grammitidaceae) stored in the Herbarium of the University of Science under Vietnam National University were studied with the traditional morphological methods. The study provides descriptions, illustrations and comparisonsof 6 species of genus Prosaptia, namely P. alata, P. barathrophylla, P. intermedia, P. pectinata, P. obliquata and P. contigua. Prosaptia contigua (G.Forst.) C.Presl has been identified as a new record for the flora of Vietnam